Analisis Life Cycle Costing Pengolahan Kopi Robusta Natural Process (Studi Kasus di KSU Ketakasi Sidomulyo) - Ervina Nur Khasanah (Fakultas Teknologi Pertanian, 2025)
Coffee is one of the agricultural commodities that has a high level of price volatility. Coffee prices experience significant fluctuations over time, both in the national and international markets. The purpose of this study was to determine the cost components in the robusta coffee production process, calculate the life cycle cost of robusta ketakasi coffee using life cycle costing (LCC), and provide recommendations in the cost management system in the robusta ketakasi coffee production process. The research method used is life cycle cost, which is an approach to calculating the total cost of a product during its life cycle. The results showed that the total cost per unit of 250gram robusta ground coffee product was Rp. 25,463.26 with a total life cycle cost of Rp. 4,048,924,413. The largest expenditure came from the purchase of raw materials of Rp. 20,000 per unit which is included in the life cycle operation and maintenance costs (Com). In addition, this study also used sensitivity analysis to evaluate the impact of changes that might occur. The sensitivity analysis of the ketakasi ground coffee business was carried out on the increase in the price of raw materials, namely coffee beans and the decrease in the selling price of the product, which showed that both scenarios were sensitive. Based on these results, the recommendation results can be seen by increasing the selling price of Robusta ground coffee products.
Reuploud Repository hasyim Juni 2026 :: Finalisasi Repositori File 10 Juni 2026_Kurnadi
Keywords: Robusta ground coffee; life cycle cost; production